Creatine salts provide neuroprotection even after partial impairment of the creatine transporter. (6th January 2017) - Adriano, E.; Garbati, P.; Salis, A.; Damonte, G.; Millo, E.; Balestrino, M.
Highlights: Creatine is a compound that is critical for energy metabolism of nervous cells. Creatine absence due to deficit of creatine transporter causes severe brain symptoms. Creatine crosses BBB and neuronal membrane slowly, and only using its transporter. Creatine derivatives may cross BBB and neuronal membrane without the transporter. Creatine derivatives may be a useful strategy in creatine transporter deficiency. Abstract: Creatine, a compound that is critical for energy metabolism of nervous cells, crosses the blood-brain barrier (BBB) and the neuronal plasma membrane with difficulty, and only using its specific transporter. In the hereditary condition where the creatine transporter is defective (creatine transporter deficiency) there is no creatine in the brain, and administration of creatine is useless lacking the transporter. The disease is severe and incurable. Creatine-derived molecules that could cross BBB and plasma membrane independently of the transporter might be useful to cure this condition. Moreover, such molecules could be useful also in stroke and other brain ischemic conditions. In this paper, we investigated three creatine salts, creatine ascorbate, creatine gluconate and creatine glucose. Of these, creatine glucose was ineffective after transporter block with guanidine acetic acid (GPA) administration. Creatine ascorbate was not superior to creatine in increasing tissue creatine and phosphocreatine content after transporter impairment, however even after such impairment it delayed synaptic failure during anoxia. Finally, creatine gluconate was superior to creatine in increasing tissue content of creatine after transporter block and slowed down PS disappearance during anoxia, an effect that creatine did not have. These findings suggest that coupling creatine to molecules having a specific transporter may be a useful strategy in creatine transporter deficiency. In particular, creatine ascorbate has effects comparable to those of creatine in normal conditions, while being superior to it under conditions of missing or impaired creatine transporter.